Vertebrobasilar dolichoectasia presenting as symptomatic obstructive hydrocephalus: A case report with review of literature - Roopa Seshadri; Nishant Sadashiva; Dhaval Shukla; Jitender Saini; Paritosh Pandey (Indian Journal of Neurosurgery)
Vertebrobasilar dolichoectasia (VBD) is a common, but usually asymptomatic condition characterized by marked elongation, dilatation, and tortousity of the vertebral and basilar arteries. VBD can sometimes present with symptoms related to mass effect like cranial nerve palsies, or with ischemia or hemorrhage. Hydrocephalus is an extremely uncommon presentation of VBD. We describe here a patient with VBD who presented with symptomatic hydrocephalus due to third ventricular obstruction, which was relieved by ventriculoperitoneal shunt.